A LINGUISTIC LANDSCAPE IN HEALTH CONTEXT: A STUDY CASE IN TWO CAMPUSES IN A TOWN - Fiki Fauzi; Khristianto Khristianto (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
This article focuses on a linguistic landscape that appear in Faculty of Health Universitas Muhammadiyah Purwokerto and Health Polytechnic Semarang. The aims of this study is to compare the linguistic landscape in two faculty of health which were in Universitas Muhammadiyah and Health Polytechnic Semarang. The writers use the theory from Spolsky and Cooper to analyze the linguistic landscape according to the language used in the sign and according to the function of the signs. The writers also used observation instrument. Thus, the writers visited both places and take a pictures ome signs that appeared. There are two dominant languages found among those selected sites. Those language are English language and Indonesian language. Six types are provided to categorize the linguistic landscape: direction signs, advertising signs, warning notices and prohibitions, building names, informative signs, and instructions. Furthermore, the functions of linguistic landscape for students are as motivation, the form of hopes from campus to students, for the media for communication, information, and creating a culture. Keywords: public sign, health department, language, landscape.